PMC-Labeling of Certain Classes of Graphs - R Ponraj; S Prabhu; A M S Ramasamy (Diponegoro University, 2025)
In this paper, we investigate the PMC-labeling behavior of some new graphs such as the double fan graph, triple fan graph, m–enriched fan graph, C_n–snake, stripe blade graph, G_n, Sf_n + K_1, armed helm graph, alternate armed helm graph and spectrum graph.